Implementasi Al-Akhlak Lil Banin Jilid 3 terhadap Akhlak Santri Kelas I’dad di Pondok Pesantren Sirojul Huda Bogor - Nurwahdi, Nurwahdi; Pesha, Indry Nirma Yunizul; Alfaien, Noor Isna (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research discusses the implementation of the book Al-Akhlaq Lil Banin volume 3 at the Sirojul Huda Islamic Boarding School in Bogor, which aims to improve the morals of i'dad class students to form the character of faith, piety and noble character. The focus is on how to implement this book in forming the character of students as well as the supporting and inhibiting factors. The research uses qualitative methods with field studies through observation, interviews, and documentation. Data analysis was carried out by condensing data, presenting and drawing conclusions. The research results show that after studying the book and following the teacher's example of behavior, students can implement the teachings of Al-Akhlaq Lil Banin in their daily lives. The environment also plays a role as a supporting and inhibiting factor in its implementation.